Healing efficacy of methanol extract of leaves of Alternanthera brasiliana Kuntze in aged wound model - Barua, Chandana Choudhury (Medknow Publications & Media Pvt Ltd, 2012)
The methanol extract of Alternanthera brasiliana Kuntze (Family: Amaranthaceae) leaf was investigated for its wound healing effect by excision wound model (in vivo) in aged Sprague Dawley rats. In excision wound model, compared to the control group, percent contraction of wound was significantly (P < 0.01) higher in A. brasiliana-treated group (5% w/w ointment). The collagen, elastin, and hydroxyproline contents of the granulation tissue of A. brasiliana-treated group increased significantly (P < 0.01) compared to the control group, indicating better wound healing activity of the test plant. These findings were also confirmed by histopathological examination. The results suggested that methanol extract of A. brasiliana possesses significant wound healing potential in aged animal wound model.